2015
DOI: 10.2131/jts.40.349
|View full text |Cite
|
Sign up to set email alerts
|

The role of NF-κB in PARP-inhibitor-mediated sensitization and detoxification of arsenic trioxide in hepatocellular carcinoma cells

Abstract: -The therapeutic efficacy of arsenic trioxide (ATO) for treatments of solid tumors is restricted by its drug resistance and chemotoxicity. In this study, we investigated ATO sensitization and detoxification effect of the Poly (ADP ribose) polymerase-1 (PARP-1) inhibitor 4-Amino-1,8-naphthalimide (4AN) in the hepatocellular carcinoma cell line HepG2. We firstly reported that ATO treatment induced the activation of Nuclear factor of κB (NF-κB) and its downstream anti-apoptosis and pro-inflammatory effectors in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Studies have shown that ATO was an effective therapeutic agent in APL with 63.8 to 93% high remission rate and could prolong patients' survival rate (13). A number of studies also have revealed a pro-apoptotic activity of ATO in solid tumors, including breast cancer, gastric cancer, hepatocellular carcinomas and sarcoma (14)(15)(16)(17). Although ATO is able to improve the disease outcome, of note, ATO also introduces to common side effects such as gastrointestinal disorders, cough, fatigue, skin rash, myelosuppression and the most burden are the liver function failure and cardiac toxicity (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ATO was an effective therapeutic agent in APL with 63.8 to 93% high remission rate and could prolong patients' survival rate (13). A number of studies also have revealed a pro-apoptotic activity of ATO in solid tumors, including breast cancer, gastric cancer, hepatocellular carcinomas and sarcoma (14)(15)(16)(17). Although ATO is able to improve the disease outcome, of note, ATO also introduces to common side effects such as gastrointestinal disorders, cough, fatigue, skin rash, myelosuppression and the most burden are the liver function failure and cardiac toxicity (18).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB activation is also correlated with the down-regulation of the pro-apoptotic proteins Bax and Bad (Cao et al, 2013). The activity of NF-κB in hematologic malignancies and different solid tumors has been associated with anti-cancer drug resistance (Prasad et al, 2010; Luo et al, 2015). Inhibition of NF-κB signaling represents an effective strategy to improve the effectiveness of conventional anti-tumor drugs (Longley and Johnston, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our findings showed that 2 μM ATO exhibited the similar cytotoxicity to 10 nM FK866 in both cancer cell lines. Most noticeably, the regimen of ATO-FK866 combination showed synergistic cytotoxicity even at very low concentration of 2 μM ATO (2–50 μM represents the ATO dosage used in clinics for cancer chemotherapy (32). Meanwhile, cell apoptosis was dramatically increased in both OSCC cell lines after treatment with ATO or ATO-FK866 combination, which underlines the mechanism of the inhibition of cell viability by ATO.…”
Section: Discussionmentioning
confidence: 99%